Design of Virtual Tourism In Ciwidey Area, Bandung District - Widiarrachman, R Fajar; Putra, Rifki Rahmanda (Politeknik Negeri Bandung, 2023)
The COVID-19 pandemic in 2020 significantly impacted various sectors, including tourism, leading to restrictions on community activities. This study focuses on the aftermath of the pandemic and explores virtual tourism as a recovery strategy. The authors propose a virtual tourism platform developed using the Multimedia Development Life Cycle, concentrating on the Ciwidey area with attractions like Kawah Putih and Situ Patengan. Qualitative methods were employed, including interviews and documentation studies involving industry, Academia, and government representatives as informants. The Ciwidey area's unique features, characterized by captivating landscapes, were harnessed for virtual tourism content. The author utilized a multimedia approach, incorporating video, text, photos, and sound on a web platform, prioritizing high-quality 360° x 180° videos and drone views. To ensure user satisfaction, the author conducted testing and evaluated navigation ease, cognitive content, information presentation, media integration, artistic aesthetics, and overall functionality. The website, stored on hosting, is accessible globally through the World Wide Web (WWW) in a responsive format, enhancing user experience across different devices. This innovative approach aims to revitalize the tourism sector by offering an engaging virtual experience, adapting to the changing landscape caused by the pandemic.